2006
DOI: 10.1038/sj.jp.7211583
|View full text |Cite
|
Sign up to set email alerts
|

The impact of single family room design on patients and caregivers: executive summary

Abstract: Objective: To explore the implications of the single family room (SFR) care environment of neonatal intensive care units (NICU) compared to Open-bay, Combination and Double-occupancy configurations, focusing on family experience, neonate outcomes, staff perceptions, cost and environmental design. Study design:This study uses a multimethod design with 11 Level III NICUs. Space allocations, construction costs, staff preferences and perceptions, and occupant behaviors were evaluated.Results: SFR NICU design provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
112
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(118 citation statements)
references
References 33 publications
3
112
0
3
Order By: Relevance
“…Caregivers, too, recognize that an SFR design improves the sensory environment for newborns and is more desirable for families, but creates communication and collaboration impediments for both families and staff that are not found in open, multi-bed rooms. [3][4][5] In this issue, two studies using historical controls of multi-bed NICUs showed that moving to a new SFR NICU may improve staff perception of workplace quality (Stevens et al 6 ), but this is dependent to some degree on the type of caregiver and the length of time after the move during which the caregivers are surveyed (Domanico et al 7 ). Furthermore, the Domanico study showed that caregiver concerns must be considered subjective, as the perception that the safety of the infant might be compromised in the SFR could not be confirmed by increases in mortality or length of stay.…”
Section: Gustave Le Bonmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregivers, too, recognize that an SFR design improves the sensory environment for newborns and is more desirable for families, but creates communication and collaboration impediments for both families and staff that are not found in open, multi-bed rooms. [3][4][5] In this issue, two studies using historical controls of multi-bed NICUs showed that moving to a new SFR NICU may improve staff perception of workplace quality (Stevens et al 6 ), but this is dependent to some degree on the type of caregiver and the length of time after the move during which the caregivers are surveyed (Domanico et al 7 ). Furthermore, the Domanico study showed that caregiver concerns must be considered subjective, as the perception that the safety of the infant might be compromised in the SFR could not be confirmed by increases in mortality or length of stay.…”
Section: Gustave Le Bonmentioning
confidence: 99%
“…Caregivers, too, recognize that an SFR design improves the sensory environment for newborns and is more desirable for families, but creates communication and collaboration impediments for both families and staff that are not found in open, multi-bed rooms. [3][4][5] …”
mentioning
confidence: 99%
“…11,15 -17 This belief has coincided with a shift in new NICU construction away from the traditional OU design to NICU's with greater attention to acoustically favorable materials, and variable lay-outs, most notably, the single-family room (SFR) design. 18,19 These design modifications would be expected to favorably impact most factors contributing to overall sound levels within an NICU, which include the overall unit design, the acoustic qualities of the room (heating, air-conditioning and ventilation) and design-influenced modifications in human behavior and operational activity. However, the use of common NICU equipment is a noise variable that may remain significant despite the above improvements.…”
Section: Introductionmentioning
confidence: 99%
“…9 As a direct result of these factors, the traditional open-bay NICU (OPBY) environment may have contributed greatly to increased stress, 10 poorer perceptions of satisfaction with the nursery environment and poorer perceptions of the quality of the care provided among NICU staff. 11,12 An architectural solution proposed for many of these problems is the single-family room (SFR) NICU design. 13,14 When used in conjunction with appropriate methods to control the environmental factors that impact the tiny neonate together with the institution of family centered 8 and developmental care, 15,16 the SFR NICU is hypothetically superior to the conventional OPBY facility both from the standpoint of improved physiologic stability and better long-term infant development.…”
Section: Introductionmentioning
confidence: 99%